(untitled) (Argos, 2025)
This article intends to prove to what extent Callimachus" Hymn to Zeus Is a programatic poem (as Aetia’s Prologue and Epilog and Iambi I and XIII) and to analyze the means used by the poet to exhibit his program ("metaliterature" and "performance"), the narrative (mythopoetic) contents selected to achieve his aim and the semic-symbolic system constructed to express metaphorically, from within the ποίημα, this performance of his ποιεῖν. Results obtained are confronted to the "metaliterary" assertions of the Hymn to Apollo (vv. 105-113).